DNA bending by thyroid hormone receptor: influence of half-site spacing and RXR. - Shulemovich, K (1995)
Transcriptional activation by thyroid hormone (T3) requires interactions between the T3 receptor (TR) and T3 response elements (TREs) composed of two copies of sequences related to AGGTCA. Direct repeats of this sequence are a functional TRE when spaced by 4 but not by 5 bp (DR4 versus DR5). TR bound as monomers, homodimers and heterodimers with retinoid X receptor (RXR) to both DR4 and DR5, with an approximately 10-fold greater affinity for DR4 due to reduced dissociation of the protein-DNA complex. We explored DNA bending as an additional variable which could influence the transcriptional outcome of the TR-TRE interaction. Circular permutation indicated a large distortion of the DNA following TR binding, but phasing analysis strongly suggested that this was due only in small part to DNA bending. Phasing analysis indicated that both TR/RXR and TR homodimer induced bends of approximately 10 degrees in DR4, but caused little bending of DR5. Moreover, the TR homo- and heterodimers bent DR4 in opposite directions. These results indicate that in addition to regulating the affinity and spacing requirement for DNA binding by TR, the TR dimer partner may also modulate transcription by influencing the direction of the bending induced by TR binding to DNA, although this effect may be subtle, due to the modest degree of bending.